2017
DOI: 10.5539/ass.v13n5p7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grandparents’ Co-parenting on Young Children’s Personality and Adaptation: Chinese Three-generation-families

Abstract: Due to the prevalence of grandparents' co-parenting of children in China, this study aimed to examine its influence on young children's personality and adaptation. With the cooperation of a kindergarten in Shanghai, 530 parents of children 3-6 years of age were invited to answer the questionnaire after giving their consent, and 422 of the questionnaires were effective. Three factors were extracted by Exploratory Factor Analysis for children's temperament: Fearfulness in Strange Situations (FS), Intensity of Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Since the concept of non-cognitive skills is borrowed from psychology, some psychology studies have found adverse influences of grandparental care on children's mental health in China (e.g., Sun & Jiang, 2017). Our study is different from previous psychology studies on this topic in three aspects.…”
Section: Literature Reviewmentioning
confidence: 63%
“…Since the concept of non-cognitive skills is borrowed from psychology, some psychology studies have found adverse influences of grandparental care on children's mental health in China (e.g., Sun & Jiang, 2017). Our study is different from previous psychology studies on this topic in three aspects.…”
Section: Literature Reviewmentioning
confidence: 63%
“…An important relationship with a nonparent caretaker might well alter attachment relationships with parents. 30,31 This possibility in a joint family system can thus account for such findings. Another attachment relationship may take precedence and be correspondent with attachment to God.…”
Section: Discussionmentioning
confidence: 87%
“…Perhaps in a joint family system, the presence of increased number of family members allows for substitute attachment figures such as grandparents. 30,31 The joint family system may provide an opportunity for multiple attachment relationships and, therefore, greater fluidity in future attachments, particularly the attachment to God. The idea of parental attachment as a blueprint 6,8,9 for other attachment relationships may not hold true in collectivistic cultures where there are multiple close caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Grandparent coresidence and involvement in childcare can also be driven by familism values and norms. Many studies that collected data from kindergartens in Chinese urban areas showed negative effects of grandparental care (X. Li & Liu, 2019; Sun & Jiang, 2017), while grandparental care in rural areas was often found to be positive or without significant effects (S. Guo et al, 2019; Zeng & Xie, 2014). The domestic floating population in China increased from 78.76 million in 2000 to 170.6 million in 2010 (Liang, 2016).…”
Section: The Effects Of Grandparental Carementioning
confidence: 99%
“…Using fixed effects regressions, He and Wang (2021) found that three-generational household arrangement in United Kingdom has a negative effect on children's cognitive and behavioral outcomes in early childhood, but such arrangement matters less for children during middle childhood and adolescence. Sun and Jiang (2017) examined the grandparenting effects of kindergarten children in Shanghai, and found that children raised only by parents had higher prosocial activity than those raised dually by parents and grandparents and lower anxious preoccupied attachment than those raised only by their grandparents. Moreover, in rural areas of China, grandparental care for left-behind children often suffers from negative labels and stigmas (S. Guo et al, 2019).…”
Section: The Effects Of Grandparental Carementioning
confidence: 99%